Discontinuity of outpatient follow-up of risk children: perspective of mothers - Ieda Aparecida Diniz; Bárbara Radieddine Guimarães; Juliana Barony da Silva; Tatiana Silva Tavares; Elysângela Dittz Duarte (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: to identify aspects that contribute to the discontinuation of outpatient follow-up of newborns from Neonatal Intensive Care Units (NICU) from the perspective of mothers. Method: exploratory, qualitative study, whose theoretical framework was Symbolic Interactionism. Fifteen mothers of children with NICU who discontinued outpatient follow-up in Belo Horizonte-MG were included in a semi-structured interview. Data were analyzed based on the proposal of Hsieh and Shannon. Results: distance from the health service, absence of family support, difficulty in leaving work, maternal health status, organization of the health service itself and deficiency of public transportation were predisposing factors for outpatient abandonment. Mothers understand that their children do not need differentiated care of children at usual risk. Conclusion: service organization, socioeconomic status of the family and social support perceived by mothers were related with the lack of compliance with outpatient follow-up.